'They' are or 'we' are? An analysis of Facebook interaction effects on brand loyalty. (2016) - Ho, Ching-Wei
The purpose of this study was to investigate how Facebook fans' relationships interact with four elements of the brand community (i.e., brand, product, company, and other fans). The study also explored the mediating effect on loyalty of the fans' relationships with these four elements by considering trust and community identification. A consumer survey via questionnaire was conducted in this research to examine the proposed hypotheses. The results of this study indicated that communities operating on Facebook fan pages can enhance trust and community identification, as well as loyalty, by improving fans' relationship with the brand, the product, the company, and other fans. Also, this study focused on the mediating role of trust and community identification, and found that the mediation effect differs depending on the type of fan relationship.